The Triple Bottom Line Accounting from Scientia Sacra Perspective - Nur Astri Sari; Yuni Shara; Sri Isnawati; Novrys Suhardianto (Universitas Muhammadiyah Surakarta, 2023)
The purpose of this article is to analyze the concept of Triple Bottom Line Accounting in the perspective of Scientia sacra. The alignment of Triple Bottom Line accounting in the Scientia sacra perceptive is essential to deal with crises in all aspects of life in terms of carrying out corporate sustainability. Scientia sacra is the knowledge of reality that is at the heart of every revelation obtained through revelation and the intellectual intuition that envelops the hearts and minds of man. This article uses interpretative method. The concept of triple bottom line in Scientia sacra's perspective is analyze in ontological, epistemological, and axiological meanings. In the ontological aspect of scientia sacra refers to the existence of God. In line with that, ontological aspect in triple bottom line also refer to the existence of God through religious-ecocentrism or spiritual dimension. In the epistemological aspect, the triple bottom line uses eco-theological principles that originate from the scriptures. In the axiological aspect, the triple bottom line has a transformative function from profit oriented to 3P (profit, people, planet) oriented. However, this transformative function has not yet fully achieved since some companies still committed irregularities, such as environmental pollution as a result from the company's business activities.Keywords: Scientia sacra, Triple Bottom Line, Ontological, Epistemologis, Axiological.